AN EXAMINATION OF THE RELATIONSHIPS BETWEEN STUDY ALONG WITH WORK LEVELS PRACTICED IN PIANO LESSONS AND CERTAIN VARIABLES - Mehtap AYDINER UYGUN (Fırat University, 2019)
The purpose of this study is to examine the relationships between levels of study along with work levels practiced by prospective music teachers in piano lessons and certain variables. These variables are class, type of high school graduated from, gender, the number of students between whom the weekly course hours are split, working area of piano lessons, academic success level in piano lessons, the type of the in